Effect of Algae and Plant Lectins on Planktonic Growth and Biofilm Formation in Clinically Relevant Bacteria and Yeasts. (9th June 2014) - Vasconcelos, Mayron Alves; Arruda, Francisco Vassiliepe Sousa; Carneiro, Victor Alves; Silva, Helton Colares; Nascimento, Kyria Santiago; Sampaio, Alexandre Holanda; Cavada, Benildo; Teixeira, Edson Holanda; Henriques, Mariana; Pereira, Maria Olivia
Abstract : This study aimed to evaluate the abilities of plant and algae lectins to inhibit planktonic growth and biofilm formation in bacteria and yeasts. Initially, ten lectins were tested on Staphylococcus epidermidis, Staphylococcus aureus, Klebsiella oxytoca, Pseudomonas aeruginosa, Candida albicans, and C. tropicalis at concentrations of 31.25 to 250  μ g/mL. The lectins from Cratylia floribunda (CFL), Vatairea macrocarpa (VML), Bauhinia bauhinioides (BBL), Bryothamnion seaforthii (BSL), and Hypnea musciformis (HML) showed activities against at least one microorganism. Biofilm formation in the presence of the lectins was also evaluated; after 24 h of incubation with the lectins, the biofilms were analyzed by quantifying the biomass (by crystal violet staining) and by enumerating the viable cells (colony-forming units). The lectins reduced the biofilm biomass and/or the number of viable cells to differing degrees depending on the microorganism tested, demonstrating the different characteristics of the lectins. These findings indicate that the lectins tested in this study may be natural alternative antimicrobial agents; however, further studies are required to better elucidate the functional use of these proteins.